An Ion-Optical Circuit of a Small-Sized Mass-Spectrometer for the Isotope Analysis of Hydrogen–Helium Mixtures - Sachenko, V. D.; Yakushev, E. M.; Nazarenko, L. M.; Antonov, A. S.; Gall, L. N.; Gall, N. R.; Berdnikov, A. S. (Journal of analytical chemistry (New York, N.Y.), 2020)
We discuss an ion-optical system (IOS) of a mass spectrometer designed for isotopic measurements of light gases, containing a magnetic prism with plane-parallel pole tips and two sector-wise, cylindrical-capacitor identical in geometry, symmetrically located relative to the prism. The relationships between the geometric parameters of the capacitors and the prism are given, which are necessary to ensure achromatic focusing of the ion beam in the plane of the detector receiving slit. We assessed numerically the effect of IOS aberrations on the mass resolution of the IOS and determined the optimal emittance of the ion beam at the source output, which enables achieving a resolution at the level of 3000–3500 with an output slit of the ion source of approximately 50 μm, high transmittance of the mass analyzer, small dimensions of the magnetic prism, and a moderate total length of the central ion trajectory (less than 1 m). The IOS is characterized by a high dispersion in masses, which is much larger than the dispersion of conventional sector magnetic mass spectrometers of the same dimensions. The IOS consists of simple geometry elements, which reduces the costs of its implementation and makes the mass spectrometer technologically advanced and convenient to set up and operate.